A calibration algorithm for maze micromouse continuous smooth turning. (1st January 2014) - Cai, Jianping; Zheng, Zengwei; Guo, Minyi
The excellent micromouse performance in a maze competition needs good sensing ability, superior walking ability, optimised intelligent algorithm and strong structure in micromouse design and manufacture. In micromouse competition, turning technology has significant effects on promoting a micromouse performance in maze walking process. The smooth turning algorithm has the advantage of finishing right-angle turns continuously without stopping. A micromouse would finish the turning more smoothly and stably while keeping a high speed, meanwhile, valuable maze solving time and spurting time could be saved for achieving better scores in competitions. In this paper, pros and cons of the algorithm are both presented. Furthermore, the main risk in smooth turning is that many single turning distance errors are accumulated to a big position error in the maze and would result in fault crashes to the maze wall. Therefore, a set of calibrating countermeasures to correct errors accumulated in continuous turning is provided as well.